2020
DOI: 10.33267/2072-9642-2020-2-26-29
|View full text |Cite
|
Sign up to set email alerts
|

Substantiation of a Line Intended for the Primary Processing of Oil Flax Into Fiber

Abstract: Департамент научно-технологической политики и образования Федеральное государственное бюджетное научное учреждение «Российский научно-исследовательский институт информации и технико-экономических исследований по инженерно-техническому обеспечению агропромышленного комплекса»

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a result of chemical analyses, it was found that the fire contains components such as cellulose, lignin, watersoluble substances, ash and pectin substances. Table 1 shows the percentage of noncellulose components of the woody part of the bast stalk [4].…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 99%
“…As a result of chemical analyses, it was found that the fire contains components such as cellulose, lignin, watersoluble substances, ash and pectin substances. Table 1 shows the percentage of noncellulose components of the woody part of the bast stalk [4].…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 99%